USE OF PSYCHOLOGICAL TRAINING IN PROFESSIONAL DEVELOPMENT OF LIBRARY STAFF - Makeeva, Irina I. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The concept of psychological training is analyzed in this paper. The experience of its using in the system of professional development of Scientific Library personnel of Oles Honchar Dnipropetrovsk National University is presented.